La Mesure: Relationships of Love and Communication in the "Lais" of Marie de France - Steffler, Micah (University of Ottawa (Canada), 2010)
This project examines the Lais of Marie de France with specific focus on "Chevrefoil," "Laustic," "Milun," and "Eliduc." The view of the relationship between orality and textuality as a linear chronological development is called into question in the light of Marie's devotion to mesure. The association between the oral and written traditions of storytelling is shown to be based on mutual co-dependency instead of a hierarchy by which the written tradition is deemed a superior mode of communication. Mesure is crucial to the maintenance of balance in this relationship, and appears in further aspects of the Lais, including the language; the connections between writing, reading, and performance; and relationships between characters. To achieve the status of fine amur, the partners in a romantic relationship must possess mesure. Lovers must value each other as equals, or a hierarchy introduces demesure into the relationship. This project reveals Marie's dedication to the importance of sustaining mesure in the face of temptation to indulge in demesure.
Keywords: Literature, English.